Overview of Hemoglobin in Rejected Donors at PMI in 2020-2021 and Influencing Factors (Jaringan Laboratorium Medis, 2023)
Hemoglobin or Hb is a protein found in red blood cells. This protein makes blood red. At normal levels, hemoglobin has many functions for the body, so normal hemoglobin levels need to be maintained. Apart from giving color, hemoglobin also functions to help red blood cells get their natural shape, which is round with a flatter center. With this shape, red blood cells can easily move and flow in the blood vessels. The normal level of hemoglobin before blood donation is 12.5 - 17.0 gr/dL%. (Regulation of the Minister of Health Number 91 of 2015). Hemoglobin levels that are too high also indicate health problems in the body. The requirements to become a donor need to be fulfilled to protect patients who will receive blood transfusions, as well as to protect the donors themselves. Initial screening is done to see if the donor is healthy and fit to donate blood. In the practice of blood donation, donor suspensions are often encountered, namely donors who are rejected before making a donation (Larasati, 2016).